2022
DOI: 10.3389/fcell.2022.874828
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics analysis reveals the mechanical stress-dependent changes in trabecular meshwork cytoskeletal-extracellular matrix interactions

Abstract: Trabecular meshwork (TM) tissue is subjected to constant mechanical stress due to the ocular pulse created by the cardiac cycle. This brings about alterations in the membrane lipids and associated cell–cell adhesion and cell–extracellular matrix (ECM) interactions, triggering intracellular signaling responses to counter mechanical insults. A loss of such response can lead to elevated intraocular pressure (IOP), a major risk factor for primary open-angle glaucoma. This study is aimed to understand the changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 172 publications
0
25
0
Order By: Relevance
“…In our recent work (38) on HTM cells subjected to mechanical stress, we showed a significant increase in the N-SREBP2 that is involved in cholesterol biogenesis. To better understand the mechanosensing functionality of SREBPs, here we provide empirical evidence by utilizing multiple systems to qualitatively and quantitatively assess the potential changes in SREBPs localization under mechanical stress.…”
Section: Mechanosensing Via Srebps Activation In Htm Cells Aids In In...mentioning
confidence: 75%
See 3 more Smart Citations
“…In our recent work (38) on HTM cells subjected to mechanical stress, we showed a significant increase in the N-SREBP2 that is involved in cholesterol biogenesis. To better understand the mechanosensing functionality of SREBPs, here we provide empirical evidence by utilizing multiple systems to qualitatively and quantitatively assess the potential changes in SREBPs localization under mechanical stress.…”
Section: Mechanosensing Via Srebps Activation In Htm Cells Aids In In...mentioning
confidence: 75%
“…On the other hand, in vivo studies in SCAP f/f mice injected with AdCre confirmed that the molecular inactivation of SREBPs by knocking down SCAP significantly lowered IOP by 10 days post-injection. In our recent study, we observed that TM cells under mechanical stress showed increased SREBP2 protein levels (38). The SREBP2 is primarily known to contribute to cholesterol production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, genome-wide association studies (GWAS) have revealed hundreds of POAG-related genetic loci with consistent effects across ancestries ( 23 , 110 , 111 ); and whole-genome-based polygenic risk score enables the prediction of future glaucoma risks ( 112 ). Furthermore, multi-omics investigations can help identify the molecular signature for glaucoma predisposition ( 113 ), patient-specific tear composition ( 114 ), mechanical stress-derived trabecular meshwork cytoskeletal changes ( 115 ), and risk factors for IOP elevation ( 116 ). Integrating image data with multi-omics data (e.g., genomics, transcriptomics, proteomics, and metabolomics) using approaches such as spatial transcriptomics ( 117 ) may reveal novel genotype-phenotype associations and causal inferences, allowing the understanding of glaucoma-related disease etiology in a highly localized manner as well as the identification of more biologically-related glaucoma phenotypes.…”
Section: Discussionmentioning
confidence: 99%